Reintegrating Afghan Insurgents - Jones, Seth G. (RAND Corporation, 2011)
Examines reintegrating Taliban and other insurgents into their local communities in Afghanistan and outlines steps to facilitate that reintegration process. The author discusses the factors that increase the likelihood of reintegrating fighters and the key options for fighters as they consider reintegration. Finally, he outlines operational and tactical steps that should be taken when insurgents consider reintegration.